KONSEP BERKAH DALAM KONSUMSI MAKANAN HALAL: TINJAUAN AL-QUR’AN DAN SUNAH - Faulika Permana, Ridani Faulika; Bandiyah, Siti Us (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2021)
Consuming halal products for Muslims is a condition for accepting acts of worship. In fact, it plays a role in shaping a person's behavior and personality, and has a major influence on the process of knowledge transfer. Ironically, the low of halal awareness makes people tend to ignore what they consume, so that blessings in life are lost. This study aims to explore the concept of blessing in halal food consumption activities using the perspective of the Qur'an and Sunna. This research is a literature study using a descriptive method with a qualitative approach. Explicitly, the Qur'an mentions God's commandment for humans to eat halal and tayyib food. This shows the relationship between the Qur'an and science, namely how nutritious and good food is to be consumed. On the other hand, Islam teaches the concept of blessing in consuming food so that it brings goodness to human life. The concept of blessing is widely discussed in the Qur'an and Sunna. This blessing is an important point in building an Islamic civilization